Diagnosis of Cancer Spread Using Percutaneous Transhepatic Biliary Cholangioscopy-guided Ultrasonography for Malignant Bile Duct Stenosis. Issue 3 (2001) - Inoue, Hirokazu
Abstract : The characteristics of sites of intramural cancer spread were examined by comparing the intraductal ultrasonography (IDUS) and wall thickening findings at sites of intramural cancer spread and non-spread, in patients with malignant bile duct stenosis who had undergone percutaneous transhepatic biliary drainage (PTBD). The subjects were ten patients with extrahepatic bile duct cancer, two with pancreatic cancer, one with cancer of the gallbladder, and one with cancer of the papilla of Vater who underwent preoperative IDUS. From these patients, 50 IDUS slices were examined with a congruent relationship with the histologic section of resected tissue. The maximum thickening, minimum thickening, maximum/minimum thickening ratio, and form factor of the medial and lateral margins of the medial hypoechoic layer were determined using diagnostic imaging, and the results were compared at sites of cancer spread and non-spread. Twelve slices were obtained from the site of stenosis, 14 from sites of cancer spread, and 24 from non-spread sites. The maximum thickening, minimum thickening, and maximum/minimum thickening ratio differed significantly between the sites of spread and the non-spread. The absolute values for wall thickening are useful for diagnosing the presence of intramural spread in patients with malignant biliary duct stenosis.